(untitled) (PANGEEA, 2025)
University youth group that is prepared for the requirements of a company alleged to evolve in a certain sense. We are dealing here with the theory essentially functionalist, which sees students as trained to reproduce values and norms of society. Many social problems facing young people have a high degree of complexity of the support to be given to them to meet them. Experts believe that it is time to develop some standards of social work practice for teens and serve as a guide for social workers in which they fulfill multiple roles. Due to budget cuts, staff and resources, these standards represent the ideals of being conquered, and some agencies and social workers will be able to meet only gradually. Keywords: students; information; counseling; young people; The main limitation of these steps is to consider youth as a transition phase from adolescence to adult life, in the case of students, university education aims at forming learning, knowledge and work skills for a future place of work. Therefore, the focus is on education in line with labor life market requirements.